Women and Tourism: Hindering Factors of Women Employment in the Hotel Sector in Sri Lanka - Kladeen, Mubarak (International Journal of Psychosocial Rehabilitation, 2020)
Empowerment opportunities for women have been proven to be more rampant in the travel and tourism industry. In certain countries, women make up 60% to 70% of the workforce in the hotel sector. Unfortunately, Sri Lanka is still experiencing a very low rate of female employment in its hotel industry. Further empirical studies could provide support for these statistics and determine the factors that hinder women from joining the workforce. This study therefore aims to investigate the factors that prevent women from working in the hotel sector in Sri Lanka, with a specific focus on socio-cultural and institutional elements. The study sample includes prospective female employees in various sectors in Sri Lanka, those with college degrees and between 20 and 40 years old. The sample selection was carried out using the non-probability convenience sampling method; 400 respondents were selected, but only 334 responses were received and usable. The findings revealed that all the socio-cultural factors had a high influence on women's employment in the hotel sector in Sri Lanka, whilst the institutional factors had a moderate influence.